2011
DOI: 10.1111/j.1364-3703.2011.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the Gp‐Rbp‐1 gene in Globodera pallida includes multiple selective replacements

Abstract: The Globodera pallida SPRYSEC Gp-Rbp-1 gene encodes a secreted protein which induces effector-triggered immunity (ETI) mediated by the Solanum tuberosum disease resistance gene Gpa2. Nonetheless, it is not known how the Andes orogeny, the richness in Solanum species found along the Cordillera or the introduction of the nematode into Europe have affected the diversity of Gp-Rbp-1 and its recognition by Gpa2. We generated a dataset of 157 highly polymorphic Gp-Rbp-1 sequences and identified three Gp-Rbp-1 evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 29 publications
0
24
0
2
Order By: Relevance
“…RanGAP2 shows less sequence size variations and a lower polymorphism rate (31.4% vs 19%) than Gp-Rbp-1 [20], the gene encoding for the effector recognized by GPA2. Furthermore RanGAP2 also appears to be less variable than the housekeeping gene nitrate reductase, whose variability was evaluated in various Solanum species [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…RanGAP2 shows less sequence size variations and a lower polymorphism rate (31.4% vs 19%) than Gp-Rbp-1 [20], the gene encoding for the effector recognized by GPA2. Furthermore RanGAP2 also appears to be less variable than the housekeeping gene nitrate reductase, whose variability was evaluated in various Solanum species [28].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Rx, Gpa2 induces a much weaker hypersensitive response (HR) when transiently expressed with its effector counterpart (the avirulence protein Gp-RBP-1 of G. pallida ) in tobacco [19]. Unexpectedly, numerous variants of the G. pallida avirulence protein GP-RBP-1 are recognized by GPA2, even those from nematode populations described as virulent against S. tuberosum cultivars expressing Gpa2 [20]. Thus, other proteins involved in the recognition of GP-RBP-1 by GPA2 may explain these results and RanGAP2 has been thought to mediate recognition of the avirulence protein GP-RBP-1 by GPA2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study revealed that eight sites are under positive selection in Gp-RBP-1, six of which were predicted to localise to the SPRY domain, including the P/S polymorphism at position 187 known to be required for recognition by Gpa2. The five novel sites in the SPRY domain were not involved in Gpa recognition but are hypothesised potentially to interact with other plant host proteins (Carpentier et al, 2012). Hallmarks of positive selection have been demonstrated in effector genes of the oomycete Phytophthora and implicated in host adaptation (Raffaele et al, 2010).…”
Section: Identification Of Root-knot and Cyst Nematode Avr Genesmentioning
confidence: 99%
“…The SPRY domain was shown to be involved in the recognition of Gp-RBP-1 by Gpa2, as the polymorphism correlating to Avr gene recognition was localised to a single amino acid in the Gp-RBP-1 SPRY domain (Sacco et al, 2009). In another study, the diversity and evolution of Gp-RBP-1 was investigated using a dataset of 157 highly polymorphic Gp-RBP-1 sequences obtained from numerous G. pallida populations collected in Peru and Chile (Carpentier et al, 2012). The study revealed that eight sites are under positive selection in Gp-RBP-1, six of which were predicted to localise to the SPRY domain, including the P/S polymorphism at position 187 known to be required for recognition by Gpa2.…”
Section: Identification Of Root-knot and Cyst Nematode Avr Genesmentioning
confidence: 99%